Epidural hematoma after ventriculoperitoneal shunt surgery: report of two cases - PEREIRA,CARLOS UMBERTO (1998)
Ventriculoperitoneal shunt operations represent the most used choice for treating hydrocephalus, although some related complications have been reported. Due to its rarity, potential dangers, and mortality rate, we present two cases of epidural hematoma following ventriculoperitoneal shunt, discussing its pathophysiology and prophylaxis.